Policing global movements: tourism, migration, human trafficking, and terrorism ; international police executive symposium - Taylor, S. Caroline (International Police Executive Symposium co-publications, 2013)
"PES Preface The International Police Executive Symposium (IPES) was founded in 1994 to address one major challenge--the worlds of research and practice remain disconnected even though cooperation between the two is growing. A major reason is that the two groups speak in different languages. The research is published in hard-to-access journals and presented in a manner that is difficult for some to comprehend. On the other hand, police practitioners tend not to mix with researchers and remain secretive about their work. Consequently, there is little dialogue between the two and almost no attempt to learn from one another. The global dialog among police researchers and practitioners is limited. True, the literature on the police is growing exponentially, but its impact upon day-to-day policing is negligible. The aims and objectives of the IPES are to provide a forum to foster closer relationships among police researchers and practitioners on a global scale, to facilitate cross-cultural, international, and interdisciplinary exchanges for the enrichment of the law enforcement profession, to encourage discussion, and to publish research on challenging and contemporary problems facing the policing profession. One of the most important activities of the IPES is the organization of an annual meeting under the auspices of a police agency or an educational institution. Now in its 17th, year the annual meeting, a fiveday initiative on specific issues relevant to the policing profession, brings together ministers of interior and justice, police commissioners and chiefs, members of academia representing world-renown institutions, and many more criminal justice elite from over 60 countries"--